2015
DOI: 10.1063/1.4916109
|View full text |Cite
|
Sign up to set email alerts
|

Site preference and compensation behavior in Co(Cr, Mn)2O4 system

Abstract: Site preference of doped Mn ions in CoCr2−xMnxO4 (x = 0–2) series has been derived separately from structure and magnetic measurement. It shows that parts of the doped Mn ions occupy the A (Co) sites when x < 0.5. And then, it takes the two B (Cr) sites in turn before and after x = 1.3. This site preference behavior results in a role conversion of the magnetic contributors and, thus, leads to the composition dependent magnetic compensation. Temperature induced compensation and negative magnetization hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
4
14
1
Order By: Relevance
“…For x = 0.8, the M(T ) also changes sign around ≈70 K and it becomes positive below ≈35 K, which is consistent with the previous reports measured at different magnetic fields [25,29]. The FC curve of the compound with x = 0.6 exhibits a change in sign around ≈80 K and remains negative until 2 K. In accordance with the previous reports, these are the usual characteristics of the ferrimagnetically ordered state, where the compensation of magnetization along the magnetic field leads to the change in sign of M(T ) [27,[30][31][32].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…For x = 0.8, the M(T ) also changes sign around ≈70 K and it becomes positive below ≈35 K, which is consistent with the previous reports measured at different magnetic fields [25,29]. The FC curve of the compound with x = 0.6 exhibits a change in sign around ≈80 K and remains negative until 2 K. In accordance with the previous reports, these are the usual characteristics of the ferrimagnetically ordered state, where the compensation of magnetization along the magnetic field leads to the change in sign of M(T ) [27,[30][31][32].…”
Section: Resultssupporting
confidence: 92%
“…However, a weak change of slope in the ZFC curve may be correlated to the low-T anomaly in (T ), pointing to a magnetoelectric coupling. The low-T anomaly is attributed to the spiral magnetic order, as suggested in the previous reports [25,27,[29][30][31][32]. In Fig.…”
Section: Resultssupporting
confidence: 78%
“…The comparative study of the electronic structure, thus, shows that the Co states are delocalised irrespective of the crystal environment while the Fe states are extremely localised in the CoB 2 O 4 compounds considered. This would have important consequences on the magnetic exchange interactions and therefore the spin structures of the pristine compounds as well as in doped systems which have been investigated experimentally only recently [9,12,13]. In the next section we compute and discuss the magnetic exchange interactions of these compounds.…”
Section: Electronic Structure and Magnetic Momentsmentioning
confidence: 99%
“…The substitution of Cr by Fe resulted in new phenomena like magnetic compensation, sign reversal of exchange bias (EB) effect [9][10][11] at a critical temperature and significant magnetostriction [12]. Recent structural and magnetic studies [13] upon substitution of Cr by Mn in CoCr 2 O 4 too showed a composition and temperature induced magnetisation compensation, along with a composition dependent structural transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Among many magnetically frustrated compounds, the family of chromate spinels MCr 2 O 4 (M = Mn, Fe, and Co) has attracted intense interest. These materials crystallize into the normal spinel structure AB 2 O 4 , with M 2+ and Cr 3+ ions occupying the tetrahedral (A) and octahedral (B) sites, respectively. As both the nearest-neighbor exchange interactions J AB and J BB are antiferromagnetic (see Figure c), a strong competition between the exchange interactions ( J BB / J AB > 2/3) causes magnetic frustration, resulting in a unique three-sublattice ferrimagnetic spiral order. , In the bulk, such a conical spiral order engenders a macroscopic spontaneous polarization which is switchable by an external magnetic field, consistent with the calculations based on the spin-current model and the inverse Dzyaloshinskii–Moriya interaction model …”
mentioning
confidence: 99%